ETHICS IN THE DESIGN OF KUHP: SPECIAL STUDY ON LGBT - Ekawati, Ekawati (Universitas Islam Negeri Alauddin Makassar, 2019)
Indonesia is a state of law that has a Muslim majority population. Issue of LGBT (Lesbian, Gay, Bisexual, and Transgender) has come to the forefront in Indonesia. Situation illustrates the debate over the legalization of LGBT in Indonesia which is still multiple interpretations (pros and cons). Some opinions state that sexual deviations of LGBT people, as long as they do not harm others certainly do not have an impact. However, several studies have mentioned a causal relationship between sexual deviation with crime. Criminal Law has regulated crimes including those arising from LGBT, but initially only focused on LGBT crimes with child victims. However, the expansion of the articles of decency has been carried out, such as adultery (Article 284), rape (Article 285) and same-sex/homosexual sexual abuse (Article 292) in KUHP.